2012
DOI: 10.1038/gene.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies novel compound heterozygous mutations of IL-10 receptor 1 in neonatal-onset Crohn's disease

Abstract: Inflammatory bowel disease is well recognized for a strong genetic involvement in its pathogenesis. Homozygous mutations in interleukin-10 receptor 1 (IL-10R1) identified by linkage analysis were shown to be involved in this disorder. However, the underlying molecular mechanism and the causal nature of the mutations in the disease process remain to be clarified. In this study, using whole exome sequencing, we identified novel compound heterozygous missense mutations in the extracellular domain of IL-10R1 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 25 publications
2
54
0
2
Order By: Relevance
“…The cell-surface expression of dysfunctional receptors is the second genetic form of AR IL-17RA deficiency to be described. The detection of surface IL-17RA should not, therefore, exclude a diagnosis of IL-17RA deficiency, as previously shown for other cytokine receptors, such as IFN-γR1 (66-69), IFN-γR2 (70,71), IL-12Rβ1 (72,73), and IL-10RA (74,75). IL-17RA deficiency has recently been reported in two siblings from Sri Lanka (60).…”
Section: Discussionmentioning
confidence: 90%
“…The cell-surface expression of dysfunctional receptors is the second genetic form of AR IL-17RA deficiency to be described. The detection of surface IL-17RA should not, therefore, exclude a diagnosis of IL-17RA deficiency, as previously shown for other cytokine receptors, such as IFN-γR1 (66-69), IFN-γR2 (70,71), IL-12Rβ1 (72,73), and IL-10RA (74,75). IL-17RA deficiency has recently been reported in two siblings from Sri Lanka (60).…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, patients' PBMCs secreted increased amounts of TNF-α and other proinflammatory cytokines after costimulation of with IL-10 and LPS (Glocker et al 2009;Begue et al 2011;Kotlarz et al 2012;Mao et al 2012;Moran et al 2013;Engelhardt et al 2013). Furthermore, in IL-10RA-mutated B cells, IL-10-induced induction of SOCS3 was reduced (Mao et al 2012). Thus, immune cells lacking a functional IL-10 receptor were unresponsive to the negative feedback regulation provided by IL-10, leading to hyperinflammatory immune responses in the intestine.…”
Section: Il-10 Receptor Deficiencies In Humansmentioning
confidence: 95%
“…Glocker et al were first to describe three distinct homozygous mutations in four patients with early onset enterocolitis (Glocker et al 2009). Subsequently, more mutations in the IL-10 receptor were found by different groups (Begue et al 2011;Kotlarz et al 2012;Mao et al 2012;Moran et al 2013;Engelhardt et al 2013). In addition to homozygous nonsense and missense mutations, compound heterozygous mutations (Kotlarz et al 2012;Mao et al 2012;Engelhardt et al 2013) and a splice site mutations (Moran et al 2013) were reported.…”
Section: Il-10 Receptor Deficiencies In Humansmentioning
confidence: 97%
See 1 more Smart Citation
“…Taking into account all reported patients with IL-10 (n 5 5), IL-10R1 (n 5 11), or IL-10R2 (n 5 19) deficiencies, [6][7][8][9][10]43 the frequency of developing lymphoma is estimated to be 36% (5 of 14) at the age of 7 years (in the absence of a previous HSCT). It is noteworthy that lymphomagenesis has not been reported in mice with impaired IL-10-mediated pathways, despite the onset of IBD, 11,44 suggesting either the existence of marked differences between mice and humans or insufficient follow-up of the mice in an adequate environment.…”
Section: Discussionmentioning
confidence: 99%